Effects of cognitive behavioral therapy on sleep disturbances and quality of life among adults with type 2 diabetes mellitus: A randomized controlled trial - Zuo, Xiaowei; Dong, Zongmei; Zhang, Peng; Zhang, Pan; Chang, Guiqiu; Xiang, Quanyong; Zhu, Xianghua; Zhou, Jinyi; Qiao, Cheng; Yang, Yongjie; Qin, Yu; Lou, Peian (Nutrition, metabolism, and cardiovascular diseases, 2020)
Cognitive behavioral therapy (CBT) is recommended as the first-line nonpharmacotherapy for sleep complaints. However, there are no studies that tested CBT for improving sleep quality and increasing quality of life (QOL) in patients with type 2 diabetes mellitus (T2DM). Therefore, this study aims to test the effect of CBT on sleep disturbances and QOL in patients with T2DM. In total, 187 participants with T2DM and comorbid poor sleep quality were included in the analysis with the control group of 93 receiving usual care (UC) only and the intervention group of 94 receiving CBT with aerobic exercise plus UC, The Pittsburgh Sleep Quality Index (PSQI), the Diabetes-Specific Quality of Life Scale (DSQLS) and the glycated hemoglobin (HbA1C) values were collected at baseline, after the 2-month intervention, and 6 months of follow-up. The CBT group had 3.03 points lower PSQI scores (95% confidence interval [CI]: 2.07–4.00, P < 0.001) and 7.92 points lower total DSQLS scores (95% CI: 4.98–10.87, P < 0.001) than the control group after 6-month follow-up. No difference was found in HbAlc between the two groups (t = −0.47, P = 0.64) after 2-month intervention, while the CBT group had 0.89 units lower HbAlc (95% CI: 0.49–1.28, P < 0.001) than the control group after 6-month follow-up. CBT is effective for sleep disturbances and can also improve sleep quality, increase QOL, and decrease glycemic levels in participants with T2DM. Chinese Clinical Trials Registration (Practical study of the appropriate technique for improvement of quality of life of the patients with type 2 diabetes in communities: ChiCTR-IOP-16008045). •Structured cognitive behavioral therapy was mastered and applied in a community setting by general practitioners.•Structured cognitive behavior therapy improved subjective sleep disturbance and increased quality of life of patients with T2DM.•Structured cognitive behavioral therapy reduced HbA1c values at 6 months following the sleep quality intervention in the community-based randomized controlled trial.